The Implementation of the Kampung Improvement Program in Semarang: Some Obstacles and Impacts - Desi Tri Susilowati; Yety Rochwulaningsih; Haryono Rinardi (Indonesian Historical Studies, 2020)
This study analyzes Kampung Improvement Program (KIP) implementation and its impact on social life in Semarang between 1978-1988 periods. The KIP program is considered successful in building and managing slum settlements in Semarang. The success of Semarang in implementing this program makes it as a pilot project for the arrangement of two cities in Southeast Asia, namely Manila and Bangkok in 1987. This study emphasizes the use of government documents and newspapers to analyze KIP implementation progress in Semarang in the period of 1978 and ended at 1988. The program implementation was divided into two major stages, KIP Urban III and KIP Urban V. From KIP program, various physical infrastructure to support basic needs, such as toilets, clean water networks, sanitation, and road paving have been built. In its development, the KIP implementation brings a new face to Semarang towards slum villages, decreases the social pathology of the communities, and develops social groups, such as empowering Integrated Health Service Port (Posyandu) and Family Welfare Program (PKK). KIP Urban III was able to complete the construction of 21 villages, while in KIP Urban V there were 35 villages, bringing the total number of 56 villages developed.